Reducing blood culture contamination rate: A quality assurance project in a Malaysian tertiary hospital - Ramli, Siti Roszilawati; Zahari, Sabarina; Sadri, Azura; Aziz, Zahrotul Farihah; Francis, Alex (International Journal of Infection Control, 2014)
Blood cultures contamination is a common scenario in Malaysian hospitals. Reducing the contamination rate of blood culture will reduce false-positive blood culture, prevent inappropriate antibiotic prescription and reduce patient management cost. This is a 6 months study specifically focused on the effects of changing the type of skin antiseptics used (70% isopropyl alcohol plus 2% chlorhexidine replacing 70% isopropyl alcohol plus povidone-iodine) and improving the knowledge and techniques of blood culture taking in a tertiary hospital. The remedial measures introduced were successful in achieving 4.34% contamination rate, which is 2.03% less than pre-remedial contamination rate (6.37%). There was a statistically significant reduction in the number of contaminants (p = 0.02) with five-fold rise in the significant blood cultures results. Better choice of skin antiseptics and good blood culture knowledge and technique may contribute to reduce number of contamination rate in blood culture.